2008
DOI: 10.1007/s10006-008-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction after removal of zygomatic intraosseous hemangioma

Abstract: We present a case report of a 30-year-old female presenting a progressive painless swelling in the malar and zygomatic regions. CT scan demonstrated a right zygomatic lesion that extended into the orbital floor and lateral orbital wall, affecting also the zygomatic arch. The biopsy revealed an intraosseous hemangioma. Treatment was performed including an en bloc resection with healthy bony margins and primary reconstruction with calvarian bone graft in association with galea-pericranium flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The indications for treatment include mass effect, high risk of hemorrhage, and cosmesis. Different types of treatments have been described including radiotherapy, embolization of the main afferent vessels, curettage, and resection [12,15] . Radiotherapy may stop the progress of the lesion but does not address the cosmetic deformity and has the risks of tissue necrosis, retardation of growth of bones and teeth, telangiectasias, and malignant degeneration [3,9] .…”
Section: Discussionmentioning
confidence: 99%
“…The indications for treatment include mass effect, high risk of hemorrhage, and cosmesis. Different types of treatments have been described including radiotherapy, embolization of the main afferent vessels, curettage, and resection [12,15] . Radiotherapy may stop the progress of the lesion but does not address the cosmetic deformity and has the risks of tissue necrosis, retardation of growth of bones and teeth, telangiectasias, and malignant degeneration [3,9] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Maxillectomy defects, maxillary sinus aplasia, and cleft deformities are even more challenging conditions. 3,4 The installation of zygomatic implants (ZIs) is one of the various techniques described in the literature to treat the atrophic maxilla, 5 and several prospective studies [6][7][8][9][10][11] have showed successful outcomes. A previous review on the survival of ZIs 12 observed that most failures were detected until 6 months after surgery, with a high 12-year cumulative survival rate (CSR).…”
Section: Introductionmentioning
confidence: 99%
“…MRI provides not only superior soft-tissue evaluation, but the high-signal enhancement in water-sensitive, T2-weighted sequences allow for assessment of fluid-filled lesions 3. Arteriograms can be utilized if there is concern for high-flow malformations and can be therapeutically advantageous if endovascular intervention is desired, though the benefits of selective embolization are believed to be limited 281213. Several clinicians in the cases reviewed ordered preoperative MRIs and arteriograms, but rarely selective embolization was utilized.…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding that occurred during biopsy procedures was controlled with local measures and cautery. En bloc resection with adequate bony margins appears to minimize the risk of massive bleeding 81321. Therefore, despite the vascular nature of these lesions, hemorrhage is a rare complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation